2018
DOI: 10.1136/jclinpath-2017-204888
|View full text |Cite
|
Sign up to set email alerts
|

Screening and functional exploration of prothrombin Arg596 related mutations in Chinese venous thromboembolism patients

Abstract: Prothrombin Arg596Gln mutation is a risk factor for Chinese patients with VTE due to its moderately decreased clotting activity but strong resistance to antithrombin inhibition. Prothrombin clotting activity screening and its encoding gene sequencing should be considered in patients with VTE when other established risk factors are absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The probands with previously reported ATR are shown in Table 2 . Most of the ATR cases had thrombotic events at a relatively young age, but some of the family members with ATR remained asymptomatic beyond 55 years old ( 5 , 6 ). Almost all patients had a strong family history and recurrence of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The probands with previously reported ATR are shown in Table 2 . Most of the ATR cases had thrombotic events at a relatively young age, but some of the family members with ATR remained asymptomatic beyond 55 years old ( 5 , 6 ). Almost all patients had a strong family history and recurrence of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wu et al has demonstrated the presence of 14 heterozygotes among 267 Chinese patients with idiopathic venous thromboembolism. 38 There is a certain parallelism between the Arg596 Prothrombin abnormalities and Arg338Lys FIX Padua. 39 The latter condition is due to a mutation in the FIX protein associated with greatly increased levels of activity (about 10 times the wild type), no bleeding, and a prothrombotic tendency that causes venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wu et al has demonstrated the presence of 14 heterozygotes among 267 Chinese patients with idiopathic venous thromboembolism. 38…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin Belgrade mutation (c.1787G>A, p.Arg596Gln) was detected in two families in Serbia, with 10 members being heterozygous carriers, and six of them developing recurrent thrombotic disorders at a young age 4 . Prothrombin Belgrade mutation was also detected in American, Japanese, Chinese, and Indian population 5–8 . Apart from influencing thrombin‐antithrombin interactions, prothrombin Belgrade mutation impacts the sodium binding region, which is important for maintenance of hemostatic balance.…”
Section: Introductionmentioning
confidence: 99%
“…4 Prothrombin Belgrade mutation was also detected in American, Japanese, Chinese, and Indian population. [5][6][7][8] Apart from influencing thrombinantithrombin interactions, prothrombin Belgrade mutation impacts the sodium binding region, which is important for maintenance of hemostatic balance. Binding of sodium improves the procoagulant function of prothrombin due to the increased fibrinogen affinity, that is, affected by the presence of prothrombin Belgrade, and therefore, may lead to a disruption of normal coagulation.…”
mentioning
confidence: 99%